Association between calf girth and peripheral artery disease in the Atherosclerosis Risk in Communities Study. Issue 3 (September 2020) - Liang, Jianwen; Zhang, Huanji; Sun, Xiuting; Liao, Lizhen; Li, Xiaoling; Hu, Xun; Du, Jianhang; Zhuang, Xiaodong; Liao, Xinxue
Highlights: There is a linear relation of gender specific calf girth with the prevalence of peripheral artery disease (PAD). Correlation of calf girth and PAD prevalence indicates there is gender interaction effect. There is a significant interactive effect of race and calf girth on incident PAD in men. Abstract: Background: The pathogenesis of peripheral artery disease (PAD) is associated with impaired calf muscle. We sought to investigate the association between gender-specific calf girth and the prevalence of PAD among participants from a community-based cohort study. Methods: A total 13, 808 participants in the Atherosclerosis Risk in Communities (ARIC) study without prior PAD were included in the final analysis. Calf girth was measured at baseline (1985–1987). A hospital diagnosis with an ICD-9 code defined incident PAD during follow up. Cox regression analysis adjusted for demographic variables and other covariates was used to estimate hazard ratios (HR) and 95% confidence interval (CI) for the association between calf girth and PAD. Results: After a medium follow-up of 25.2 years, the overall prevalence of PAD in our study was 5.2% (721/13, 808), 335 patients were women and 386 were men. The adjusted HR for PAD with calf girth as continuous variables was 0.99 (95% CI 0.95–1.04) in females and 0.93 (95% CI 0.88–0.99) in males, respectively. Moreover, interaction for gender was statistically significant between calf girth and PAD in overall population ( p  = 0.001). Conclusions: Our findings revealed a linear association of calf girth with the prevalence of PAD among male participants in ARIC.